Pengaruh Lokasi, Harga, Fasilitas, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Jasa Kamar di Hotel Ibis Budget Jakarta Daan Mogot - Zengga Zengga; Adinoto Nursiana; Chondro Suryono (Universitas Negeri Padang, 2022)
This research started from the researcher's observation of the room occupancy rate at the Ibis Budget Jakarta Daan Mogot Hotel which has decreased from month to month, presumably due to the unstable consumer purchasing decisions for room. The purpose of this research is to determine the effect of location, price, facilities, quality of service with the decision to purchase room services at the Ibis Budget Hotel Jakarta Daan Mogot. This study is a causal associative type, the population in this study are all guests who have stayed at the Ibis Budget Daan Mogot Hotel. The sampling technique is non-probability sampling, using incidental samples, that is, anyone who happens to meet the researcher can be used as a sample. with a suitable category as a data source. The number of samples in this study amounted to 100 people. The data collection technique was carried out using a questionnaire (questionnaire) using a Likert scale that had been tested for validity and reliability. Based on the results of the total respondents' achievements regarding the assessment of Location, Price, Facilities, Quality of Service carried out by Ibis Budget Jakarta Daan Mogot, it is included in the poor category because the TCR value is 66%. Based on the results of the total respondents' achievements on purchasing decisions at the Ibis Budget Hotel Jakarta Daan Mogot, the TCR value of 69% is included in the lower category. The influence of Location, Price, Facilities, Quality of Service on purchasing decisions at Ibis Budget Jakarta Daan Mogot is 65.5% and location, price, facilities, service quality have a positive and significant effect on purchasing decisions, this is because the Sig value 0.000 > 0.05.